Freedom Of Expression In The Digital Age: Balancing Rights and Responsibilities - Aung Naing; Nyein Chan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This article investigates the complexities of protecting freedom of expression in the digital age, where social media and online platforms play a critical role. The study examines the tension between free speech, misinformation, hate speech, and content moderation policies implemented by governments and tech companies. Findings suggest that a balance must be struck between upholding freedom of expression and preventing harm, calling for a regulatory approach that respects both rights and responsibilities.